Life Cycle Carbon Management in Shipbuilding : A Construction Industry Benchmark Study - Virtanen, Milla (My University, 2024)
The significant contribution of the maritime industry to global greenhouse gas emissions necessitates vigorous strategies for carbon management throughout the life cycle of a ship. While the majority of life cycle emissions for ships originate from fuel consumption during operation, the shipbuilding phase offers considerable opportunities to reduce the overall carbon intensity. This thesis investigates life cycle carbon management in shipbuilding by benchmarking the construction industry to identify best practices and ensure regulatory compliance. The goal of the study is to identify tools and principles useful for a carbon management process, while also exploring sustainability data needs. This thesis is commissioned by Meyer Turku Oy. Effective emission reduction begins with measuring the current status via life cycle assessment, guided by ISO and Greenhouse Gas Protocol standards. Understanding these, and regulations such as the Corporate Sustainability Reporting Directive and the Corporate Sustainability Due Diligence Directive, is crucial for defining the LCA scope. An overview of the general shipbuilding process provides context and highlights the challenges of the industry. A benchmarking study with the construction industry, believed to be ahead in carbon management, was conducted. Key differences between the industries include the impact of material weight on life cycle emissions, as ships are vehicles; more weight means more fuel. In addition, in the construction industry, majority of emissions derive from concrete, whereas in shipbuilding, the equivalent is steel. The benchmarking interviews findings emphasize the importance of coordinated carbon management practices, including using sustainable materials, enhancing sustainability knowledge among designers, and establishing emission limits for newbuilds. Calculating the average carbon footprint for ships is crucial to establish these limits, which can be executed based on the turnkey suppliers areas. Overall, there’s potential for cross-industry learning to enhance life cycle carbon management in shipbuilding, promoting a more sustainable maritime industry through reduced emissions.
Keywords: CSRD, carbon management, carbon footprint, sustainability, life cycle emissions, life cycle assessment, shipbuilding